Anomalous origin of the right coronary artery with concomitant myxomatous mitral valve disease: a rare coexistence. (23rd October 2014) - Imori, Yoichi; Murakami, Masato; Tanaka, Masashi; Saito, Shigeru
Abstract : A 45-year-old man previously diagnosed with myxomatous mitral valve disease was admitted to our hospital with chest pain at rest and on effort. Contrast-enhanced CT revealed that the patient's right coronary artery originated from the left sinus Valsalva, which was compressed between the aortic and pulmonary roots. This anatomical abnormality can be associated with sudden death, syncope and chest pain. Ultrasonography showed mitral valve prolapse with severe regurgitation. Surgical repair was performed, which included coronary artery bypass graft and mitral valvoplasty with tricuspid annuloplasty. The postoperative course was uneventful and the patient remains asymptomatic. This is the first description of the coexistence of an anomalous origin of the right coronary artery with myxomatous mitral valve disease.